Individual-Level Fatality Prediction of COVID-19 Patients Using AI Methods - Yun Li; Yun Li; Melanie Alfonzo Horowitz; Jiakang Liu; Aaron Chew; Hai Lan; Hai Lan; Qian Liu; Qian Liu; Dexuan Sha; Dexuan Sha; Chaowei Yang; et al. (Frontiers Media S.A., 2020)
The global covid-19 pandemic puts great pressure on medical resources worldwide and leads healthcare professionals to question which individuals are in imminent need of care. With appropriate data of each patient, hospitals can heuristically predict whether or not a patient requires immediate care. We adopted a deep learning model to predict fatality of individuals tested positive given the patient's underlying health conditions, age, sex, and other factors. As the allocation of resources toward a vulnerable patient could mean the difference between life and death, a fatality prediction model serves as a valuable tool to healthcare workers in prioritizing resources and hospital space. The models adopted were evaluated and refined using the metrics of accuracy, specificity, and sensitivity. After data preprocessing and training, our model is able to predict whether a covid-19 confirmed patient is likely to be dead or not, given their information and disposition. The metrics between the different models are compared. Results indicate that the deep learning model outperforms other machine learning models to solve this rare event prediction problem.